2019
DOI: 10.5194/acp-19-1281-2019
|View full text |Cite
|
Sign up to set email alerts
|

The observed diurnal cycle of low-level stratus clouds over southern West Africa: a case study

Abstract: Abstract. This study presents the first detailed observational analysis of the complete diurnal cycle of stratiform low-level clouds (LLC) and involved atmospheric processes over southern West Africa (SWA). The data used here were collected during the comprehensive DACCIWA (Dynamics-Aerosol-Chemistry-Cloud-Interactions in West Africa) ground-based campaign, which aimed at monitoring LLC characteristics and capturing the wide range of atmospheric conditions related to the West African monsoon flow. In this stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…The arrival of the cooler, but not necessarily moister, mass of air more than a 100 km inland facilitates the onset of Sc clouds over land Babić et al, 2019;Dione et al, 2019). The fact that this mass of 10 air is characterized by cloudless conditions when over the sea reveals the importance of the land and other local factors on the cloud formation and maintenance Babić et al, 2019;Lohou et al, 2019). Lohou et al (2019) extended the previous work and summarized the four phases leading from cloud formation to dissipation.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…The arrival of the cooler, but not necessarily moister, mass of air more than a 100 km inland facilitates the onset of Sc clouds over land Babić et al, 2019;Dione et al, 2019). The fact that this mass of 10 air is characterized by cloudless conditions when over the sea reveals the importance of the land and other local factors on the cloud formation and maintenance Babić et al, 2019;Lohou et al, 2019). Lohou et al (2019) extended the previous work and summarized the four phases leading from cloud formation to dissipation.…”
mentioning
confidence: 79%
“…To limit the complexity of our idealized experiments and focus on the interaction of the surface and boundary-layer processes, we prescribe no advection of heat or moisture at any height. Adler et al (2019) and Babić et al (2019) found cold air advection necessary for the formation of the cloud layer. Yet 20 its relevance decreased as sunrise approached, thus justifying our assumption during our time of interest.…”
Section: Model Settings and Initial Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the Dynamics-aerosol-chemistry-cloud-interactions in West Africa (DACCIWA) project (Knippertz et al, 2015), an extensive field campaign was conducted in June and July 2016 (Flamant et al, 2018;Kalthoff et al, 2018). The aim of the DACCIWA ground-based campaign was to collect a comprehensive and high-quality data set (Kalthoff et al, 2018;Bessardon et al, 2019) which enables studies of LLC characteristics; the day-to-day variability of conditions in the atmo-Published by Copernicus Publications on behalf of the European Geosciences Union. spheric boundary layer (ABL) (Kalthoff et al, 2018;Adler et al, 2019;Dione et al, 2019); and physical processes relevant for formation, maintenance and dissolution of LLCs (Adler et al, 2019;Babić et al, 2019).…”
Section: Introductionmentioning
confidence: 99%